Synthesis of diethyelenediamine-modified poly(acrylonitrile-co-acrylamide) for the adsorption of doxycycline from aqueous solution - Md Jamil, Siti Nurul Ain; Azlee, Nur Ismahusna; Subri, Nur Nida Syamimi (Faculty of Applied Sciences, UiTM, 2024)
Antibiotic residues have caused water pollution as it is consumed daily for the treatment of diseases. They are released to wastewater from the excretion by human bodies. This study explores the potential utilization of diethylenetriamine(DETA)-modified poly(AN/AM), as polymeric adsorbents for removal of doxycycline (DOX) from aqueous solutions. The FT-IR spectra revealed that the chemical modification of poly(AN/AM) with DETA was successful. The scanning electron microscopic (SEM) analysis showed that the poly(AN/AM) and DETAmodified poly(AN/AM) appear as agglomerated spherical beads with average particle size of 204 nm and 282 nm, respectively. The effect of pH, adsorbent dosage, contact time and initial concentration of DOX solution were investigated during the adsorption process. The adsorption isotherm studies are fitted well with Langmuir adsorption model with R2 value of 0.9988 which indicates monolayer adsorption process. This study showed that a polymeric material; DETA-modified poly(AN/AM) is a promising adsorbent to capture DOX from aqueous systems.